Productivity shocks and aggregate cycles in an estimated endogenous growth model - Jim Malley; Ulrich Woitek (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using a two-sector endogenous growth model, this paper explores how productivity shocks in the goods and human capital producing sectors contribute to explaining aggregate cycles in output, consumption, investment and hours. To contextualize our findings, we also assess whether the human capital model or the standard real business cycle (RBC) model better explains the observed variation in these aggregates. We find that while neither of the workhorse growth models uniformly dominates the other across all variables and forecast horizons, the two-sector model provides a far better fit to the data. Some other key results are first, that Hicks-neutral shocks explain a greater share of output and consumption variation at shorter-forecast horizons whereas human capital productivity innovations dominate at longer ones. Second, the combined explanatory power of the two technology shocks in the human capital model is greater than the Hicks-neutral shock in the RBC model in the medium- and long-term for output and consumption. Finally, the RBC model outperforms the two-sector model with respect to explaining the observed variation in investment and hours.
Keywords: C11; C52; E32; 330; endogenous growth; human capital; real business cycles; Bayesian estimation; VAR errors; Neue Wachstumstheorie; Humankapital; Real Business Cycle; Bayes-Statistik; VAR-Modell; Modell-Spezifikation; Theorie